Performance optimization and hydration characteristics of BOF slag-based autoclaved aerated concrete (AAC). (November 2022) - Jiang, Jun; Lu, Xiaolei; Niu, Teng; Hu, Yueyang; Wu, Jiaming; Cui, Wenyu; Zhao, Degang; Ye, Zhengmao
Abstract: Basic oxygen furnace (BOF) slag, a by-product of the steelmaking process, has never been effectively utilised owing to its various drawbacks. In this study, BOF slag was used as the calcareous raw material of autoclaved aerated concrete (AAC) to successfully and completely replace lime with BOF slag. Moreover, the slurry was regulated with NaOH and a thickening agent, successfully reducing bulk density from the B07 level to the B05 level without reducing mechanical performance. The reaction products of AAC were analysed using X-ray diffraction and scanning electron microscopy. The results demonstrate that the addition of BOF slag can hinder the formation of xonotlite which offsets the other negative effects of BOF slag to a certain extent. In addition, kirschsteinite and part of C2 F were involved in generating tobermorite during the autoclaving process. Highlights: Steel slag completely replaced lime as the main calcareous raw material in AAC production. The addition of steel slag showed no significant loss of strength in AAC products. The bulk density of AAC can be reduced by adjusting the W/S ratio and NaOH content. The addition of steel slag can hinder the formation of xonotlite.